2022
DOI: 10.3389/fmicb.2022.905050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Antimicrobial Growth Promoters on Performance Parameters and Abundance and Diversity of Broiler Chicken Gut Microbiome and Selection of Antibiotic Resistance Genes

Abstract: Antimicrobial growth promoters (AGPs) are commonly used in broiler production. There is a huge societal concern around their use and their contribution to the proliferation of antimicrobial resistance (AMR) in food-producing animals and dissemination to humans or the environment. However, there is a paucity of comprehensive experimental data on their impact on poultry production and the AMR resistome. Here, we investigated the effect of five antimicrobial growth promoters (virginiamycin, chlortetracycline, bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 87 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…perfringens . In contrast, no significant alterations in the microbiome diversity and the relative abundance of beneficial bacteria, particularly Lactobacillus spp., were observed [ 14 ]. Similarly, supplementing chicken diets with subtherapeutic doses of bacitracin methylene disalicylate, tylosin, and virginiamycin preferentially enriched the cecal microbiome with butyrate- and lactic acid-producing bacteria, which both have been known for their role in modulating the gut mucosal immunity and host metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…perfringens . In contrast, no significant alterations in the microbiome diversity and the relative abundance of beneficial bacteria, particularly Lactobacillus spp., were observed [ 14 ]. Similarly, supplementing chicken diets with subtherapeutic doses of bacitracin methylene disalicylate, tylosin, and virginiamycin preferentially enriched the cecal microbiome with butyrate- and lactic acid-producing bacteria, which both have been known for their role in modulating the gut mucosal immunity and host metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other studies showed that the use of different antibiotics as growing promoters, including tetracyclines, seems to be ineffective in terms of significantly influencing the density of Lactobacillus spp. [ 29 ], but therapeutic doses of enrofloxacin are more effective in facilitating a relative abundance of multidrug-resistant Enterobacteriaceae strains [ 17 ]. Interestingly, lactobacilli, non-pathogenic clostridia, and corynebacteria are recognized as microorganisms useful to improving the digestive efficiency of chicken and for their ability to extract energy from feed [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the farm level, the relative abundance of tetracycline resistance genes increased with time in the poultry litter, irrespective of antibiotic treatment administrated during the rearing cycle [ 17 ]. Similarly, a more recent work highlighted that the abundance of tetracycline genes was not influenced by the use of grown promoting doses of antimicrobials, even if the aminoglycoside resistance genes tended to be higher in the broiler supplemented with chlortetracycline [ 29 ]. Other studies confirmed that the use of therapeutic doses of antibiotics in poultry farming increases the total ARGs load in intestinal tracts [ 15 ], even if the antibiotic-free farms had a wide distribution of resistant bacteria and related ARGs, as already observed in different geographical areas [ 23 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing societal concern about the application of antibiotics in feed as growth promoters in chickens in order to improve gut health and feed efficiency, due to their contribution to the development of antimicrobial resistance (AMR) in food animals and dissemination to humans or the environment, as well as the risk of drug residues in chicken products. It has been shown that the use of antibiotics in the feed may favor the selection of resistance to more than one class of antimicrobials in the bacterial community residing in the gut of chickens [ 1 ]. Consequently, the development of new green additives as an alternative to antibiotic growth promoters (AGP) has emerged as a priority area in the feed industry and animal production [ 2 ].…”
Section: Introductionmentioning
confidence: 99%